Methodological Aspects of Governing Residential Solid Waste Management Sphere - Likhacheva Ol'ga I.; Sovetov Pavel M. (Economic and Social Changes: Facts, Trends, Forecast, 2017)
The article is based on the results of our research on government regulation of waste treatment. The goal of the first phase of the study is to substantiate methodological provisions on arranging residential solid waste management in the region (municipality). Informational and empirical base of the research was formed with the use of the data of the Federal State Statistics Service of Russia, materials of monographs, surveys on environmental policy in foreign countries, publications in periodicals, information presented on official websites of enterprises and state and municipal authorities, as well as the data that we obtained while analyzing the situation and making observations. The object of the research is organization of residential solid waste management. Our working hypothesis that we prove is the thesis that state regulation mechanisms dominate in managing the development of waste treatment sphere and that there is a possibility of limited admission of market self-regulation tools managing residential solid waste treatment in the region (municipality). When defining “waste” we note the absence of a unified approach to the definition of “residential solid waste” and discrepancies in its interpretations in the laws and regulations of state authorities of the Russian Federation, which leads to inconsistencies in organizational regulations and communication space of state and municipal management. We note that the volume of solid waste is increasing each year, their composition becomes more complex, there emerge new packaging materials derived from complex polymers that can for a long time (a hundred years and more) retain hazardous properties, which increases the burden on the ecosystem and hazards to human health. Of the total volume of residential solid waste produced in Russia about 97% goes to landfills and dumps, for which about a thousand hectares of land is allocated annually, and the waste loses its potential as a secondary resource. The responsibility for reducing negative impact of waste on the environment is “spread” among executive authorities. Having analyzed and structured existing problems in the functioning of residential solid waste management and having reviewed domestic and foreign experience of waste management, we conclude that they can be solved step-by-step with the use of system approach to managing this sphere with the increased use of program-target tools of state regulation. In this regard, we postulate a methodological basis to represent the process of managing waste treatment sphere as a set of science-based targeted impacts on the collection, storage, transportation, processing, recycling, and disposal of waste for the purpose of ensuring environmental, economic and social standards and requirements. The article proves the necessity of and prerequisites for the formation of an integrative model for managing the sphere of residential solid waste treatment at the regional (municipal) level